Substituted Aryl Piperazine Ligands as New Dual 5-Hlox/Cox-2 Inhibitors. Synthesis, Biological and Computational Studies - Mascayano-Collado, C; Vasquez-Martinez, y; Godoy-Gonzalez, F; Godoy-Gonzalez, F; Muñoz-Osses, M; Muñoz-Osses, M; Navarrete-Tudela, E (Academic Press, 2025)
Two series of cyano (1a-l) and amino (2a-l) aryl piperazines were synthesized and evaluated for their inhibitory activity against 5-lipoxygenase (5-hLOX) and cyclooxygenase-2 (COX-2). The newly designed derivatives feature diphenyl methyl (a-d), phenyl (e-h), or methoxyphenyl (i-l) groups, respectively, and demonstrated significant inhibition of 5-hLOX. Noteworthy were compounds 1b, 1 g, 1 k, 2f, and 2 g, exhibiting IC50 values ranging from 2.2 to 3.3 μM. The most potent inhibitors (1b, 1 g, 1 k, 2c, and 2f) were characterized by a competitive inhibition mechanism, with Ki values ranging between 1.77 μM and 9.50 μM. Additionally, compounds 2a, 2b, 2 g, and 2 h displayed promising dual inhibition of 5-hLOX and COX-2, with IC50 values below 15 μM. Cytotoxicity assessments against HEK293 cells revealed that the cyano derivatives (1a-l) were non-cytotoxic (CC50 > 200 μM), whereas the amino derivatives (2a-l) exhibited moderate cytotoxicity (CC50 < 50 μM). Notably, the most active derivatives against both targets were non-cytotoxic at their respective inhibitory concentrations. Computational studies, including docking and molecular dynamics simulations, indicated that compound 1 g demonstrated greater stability within the catalytic site of 5-hLOX compared to compound 2f, correlating with the higher affinity observed in kinetic assays. Furthermore, quantitative structure-activity relationship (QSAR) analyses revealed strong correlations between theoretical and experimental IC50 values (97 % for 1a-l and 93 % for 2a-l). These findings, combined with absorption, distribution, metabolism, and excretion (ADME) predictions, suggest that these derivatives are promising candidates as dual inhibitors of 5-hLOX and COX-2. © 2025 Elsevier Inc.